Differentiation of Palm-Infecting Phytoplasmas in the Caribbean Basin Using High Resolution Melt Curve Analysis of the secA Gene - Bloch, Melody (Plant disease, 2022)
Palm lethal decline is a disease that is always fatal to infected palm hosts and is caused by three species of phytoplasma in the Caribbean basin: 'Candidatus Phytoplasma palmae', 'Ca. P. aculeata', and 'Ca. P. hispanola'. Movement of these pathogens throughout the Caribbean has been documented since their discovery in Jamaica. Over time, means of confirming infections in palms have improved. Current protocols utilize quantitative PCR (qPCR) for rapid amplification and distinction of these phytoplasmas using TaqMan probes and high-resolution melt-curve analysis (HRMA) of the 16S rRNA gene. These assays either do not detect all three phytoplasmas (HRMA) or do not distinguish between the three (TaqMan). In this study, a new qPCR-HRMA assay is developed that amplifies and distinguishes all three phytoplasmas currently known to kill palms in the Caribbean. Efficiency for the primer set secA614_F/secA759_R was shown to be consistent for all species at each concentration and yielded distinct melting temperature ranges for amplicons of 'Ca. P. palmae' (73.3 to 73.4°C), 'Ca. P. aculeata' (72.9 to 73.0°C), and 'Ca. P. hispanola' (73.5 to 73.6°C). This assay is a useful new tool not only for diagnostics that will contribute to monitoring and management programs, but it will also aid in basic research by allowing rapid screening of large samples in the context of vector surveys or identification of reservoir hosts